CAUSES OF OSTEOPOROSIS, METHODS OF DETECTION, PREVENTION AND TREATMENT MEASURES. (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article provides comprehensive information on the currently widespread disease osteoporosis. Recommendations are provided on its causes and treatment methods.